2018
DOI: 10.1016/j.actatropica.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dengue vector population using remotely sensed data and machine learning

Abstract: Mosquitoes are vectors of many human diseases. In particular, Aedes ægypti (Linnaeus) is the main vector for Chikungunya, Dengue, and Zika viruses in Latin America and it represents a global threat. Public health policies that aim at combating this vector require dependable and timely information, which is usually expensive to obtain with field campaigns. For this reason, several efforts have been done to use remote sensing due to its reduced cost. The present work includes the temporal modeling of the oviposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
103
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 45 publications
(61 reference statements)
1
103
0
3
Order By: Relevance
“…In several studies, the importance of variables has been demonstrated, being the Land Surface Temperature (LST) and the Normalized Difference Vegetation Index (NDVI) both of the most used variables in Ae. aegypti models developed [68].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, the importance of variables has been demonstrated, being the Land Surface Temperature (LST) and the Normalized Difference Vegetation Index (NDVI) both of the most used variables in Ae. aegypti models developed [68].…”
Section: Introductionmentioning
confidence: 99%
“…The Ae. aegypti species is known to be adaptable to urban environments due to its inclination to being bred in artificial containers [19,21,27,28]. Spread of the causal diseases by this vector is known to correlate with the local adult vector population [29].…”
mentioning
confidence: 99%
“…Environmental conditions including precipitation, vegetation conditions, temperature, and humidity have been shown in previous works to significantly influence Ae. aegypti mosquito development [21,27,30]. After obtaining these environmental variables from satellite data, statistical and machine learning (ML) models of diseases outbreak can be used for vector population prediction [31,32].ML is a subdivision of artificial intelligence which deals with the implementation of algorithms to learn complex patterns from machine readable input data for classification and regression purposes [33,34].…”
mentioning
confidence: 99%
See 2 more Smart Citations